Micromorphology and spectroscopic characteristics of organic matter in waterlogged podzols of the upper Amazon basin - Bardy, M.; Fritsch, E.; Derenne, S.; Allard, T.; do Nascimento, N. R. [UNESP]; Bueno, G. T. [UNESP] (Elsevier B.V., 2008)
In waterlogged environments of the upper Amazon basin, organic matter is a major driver in the podzolisation of clay-depleted laterites, especially through its ability to weather clay minerals and chelate metals. Its structure in eight organic-rich samples collected at the margin and in the centre of the podzolic area of a soil sequence was investigated. The samples illustrate the main steps in the development of waterlogged podzols and belong either to eluviated topsoil A horizons or to illuviated subsoil Bhs, Bh and 2BCs horizons. Organic matter micromorphology was described, and the overall molecular structure of their clay size fractions was assessed using Fourier transform infrared (FTIR) spectroscopy and cross polarization/magic angle spinning (CP/MAS) C-13 nuclear magnetic resonance (NMR). Organic features of the horizons strongly vary both vertically and laterally in the sequence. Topsoil A horizons are dominated by organic residues juxtaposed to clean sands with a major aliphatic contribution. In the subsoil, numerous coatings, characteristic of illuviation processes, are observed in the following horizons: (i) At the margin and bottom parts of the podzolic area, dark brown organic compounds of low aromacity with abundant oxygen-containing groups accumulate in Bhs and 2BCs horizons. Their spectroscopic features agree with the observation of cracked coatings in 2BCs and the presence of organometallic complexes, whose abundance decreases towards low lying positions. (ii) By contrast, black organic compounds of high aromacity with few chelating functions accumulate as coatings and infills in the overlying sandy Bh horizon of well-expressed waterlogged podzols. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Amazon basin; podzols; soil organic matter; micromorphology; FTIR; solid-state 13C NMR